Determination of rice leaf midrib deflection in field environment by using semantic segmentation and shortest distance algorithm - Jiaqi Luo; Baisheng Dai; Penghao Chang; Rui Gao; Zhongbin Su (Computers and Electronics in Agriculture, 2023)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Unexpected shifts of dissolved carbon biogeochemistry caused by anthropogenic disturbances in karst rivers - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Jing Zhang; Xiaodan Wang (Water Research, 2023)

Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2023)

Effects of dry-salting and brine-pickling on physicochemical properties and flavor of spaghetti squash shreds - Yi Luo; Rui Wang; Hui Han; Shuo Wang; Jianxiang Ma; Chunlong Yuan; Yamei Ren (Food Bioscience, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Promoting reversibility of layered potassium cathode through interstitial doping - Xuan Xu; Xun-Lu Li; Muhammad Mominur Rahman; Jian Bao; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Zhe Mei; Zhe Qian; Enyuan Hu; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Prevalence of Ureaplasma species among patients at a tertiary hospital in China: a 10-year retrospective study from 2013 to 2022 - Ziran Wang; Mingqi Xia; Yu Chen; Zhuo Yang; Jie Yi; Lingjun Kong; Han Zhang; Guoju Luo; Rui Li; Yaling Dou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Multiphysics coupling analysis of heat pipe reactor based on OpenMC and COMSOL Multiphysics - Aoguang Wu; Weixiang Wang; Kefan Zhang; Shaoning Shen; Wenshun Duan; Rui Pan; Xiao Luo; Hongli Chen (Annals of Nuclear Energy, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

Cleanable natural-sugar-alcohol-based polyester membrane for highly efficient molecular separation - Xiongwei Luo; Yue Wang; Yaoli Guo; Qieyuan Gao; Rui Zhao; Yanyan Liu; Riri Liu; Lei Jiang; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Resources, Conservation and Recycling, 2023)

Household energy stacking and structures in Pakistan – Results from a multiple-energy study in Azad Kashmir and Punjab - Xiaoqiao Jiao; Rui Xiong; Zhihan Luo; Yaojie Li; Hefa Cheng; Audil Rashid; Guofeng Shen; Shu Tao (Journal of Environmental Sciences, 2023)

SHARAD observations for layered ejecta deposits formed by late-Amazonian-aged impact craters at low latitudes of Mars - Yizhen Ma; Zhiyong Xiao; Fanglu Luo; Wei Cao; Rui Xu (Icarus, 2023)

The impact of freezing methods on the quality, moisture distribution, microstructure, and flavor profile of hand-grabbed mutton during long-term frozen storage - Yulong Luo; Yongzhao Bi; Rui Du; Hong Yuan; Yanru Hou; Ruiming Luo (Food Research International, 2023)

Emissions and mitigation potential of endocrine disruptors during outdoor exercise: Fate, transport, and implications for human health - Rui Luo; Tao Zhang; Li Wang; Yong Feng (Environmental Research, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

Comprehensive properties of non-penetrating and penetrating deep convection precipitation in summer over the Tibetan Plateau derived from GPM observations - Rui Wang; Zhongshan Jiang; Fengjiao Chen; Wenshou Tian; Liangliang Li; Hongying Tian; Jiali Luo (Atmospheric Research, 2023)

Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Discrete element-based regression analysis of initial ground stress and application to an extra-long tunnel in China - Ming-Rui Luo; Cheng-You Zhang; Bo Wang; Yan-Hua Zeng (Bulletin of Engineering Geology and the Environment, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Review on fault-tolerant control of unmanned underwater vehicles - Fuqiang Liu; Zuxing Ma; Bingxian Mu; Chaoqun Duan; Rui Chen; Yi Qin; Huayan Pu; Jun Luo (Ocean Engineering, 2023)

Unveiling the occurrence, distribution, removal, and environmental impacts of 65 emerging contaminants in neglected fresh leachate from municipal solid waste incineration plants - Huabo Gong; Jinwen Hu; Xuan Rui; Jinming Luo; Nanwen Zhu (Journal of Hazardous Materials, 2023)

A novel calcium peroxide/attapulgite-Fe(II) process for high concentration phosphate removal and recovery: Efficiency and mechanism - Jun Luo; Jia Peng; Zhenxing Zhong; Xuejun Long; Jiazhi Yang; Rui Li; Jun Wan (Journal of Environmental Management, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Rapid imaging approach for marine controlled-source electromagnetic with deployed transmission system - Rui Yang; Xuben Wang; Meng Wang; Xianhu Luo; Ming Deng; Jianen Jing; Kai Chen (Journal of Applied Geophysics, 2023)

Controllable solvent treatment of fluorinated graphite for high power density and low cathode swelling lithium primary batteries - Sen Ma; Wen Liu; Daoming Zhang; Cheng Yang; Ying Luo; Xiaobing Lou; Rui Guo; Yong Wang; Jingying Xie (Chemical Engineering Journal, 2023)

Microwave-coordinated KOH directionally modulated N/O co-doped porous biochar from Enteromorpha and its structure–effect relationships in efficient CO2 capture - Juan Luo; Yi Chen; Huimin Huang; Rui Ma; Ning Ma; Feng Yan; Jiyun Xu; Junshen Zhang; Jiashan Chen; Shichang Sun (Chemical Engineering Journal, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Epidemiology, genetic diversity, and evolutionary dynamics of Tembusu virus - Peng Zhou; Bin Ma; Yuan Gao; Yumin Xu; Zhuofei Li; Hui Jin; Rui Luo (Archives of Virology, 2023)

Phytoplankton control by stocking of filter-feeding fish in a subtropical plateau reservoir, southwest China - Chaoshuo Zhang; Feng Mei; Bin Luo; Dongxu Zhang; Xinyu Cheng; Yongying Xiong; Jianghui Bao; Rui Duan; Hao Jiang; Erik Jeppesen; Ming Duan (Frontiers in Marine Science, 2023)
Stocking of filter-feeding fish (mainly Hypophthalmichthys molitrix and Aristichthys nobilis ) is a common method used in lakes and reservoirs in (sub)tropical China to control phytoplankton, but the results are ambiguous and lack long-term data to support. We analysed a decade (2010-2020) of monitoring data from a subtropical plateau reservoir, southwest China, to which filter-feeding fish were stocked annually. We found that the total phytoplankton biomass, cyanobacteria biomass and average individual mass of phytoplankton decreased significantly during the study period despite absence of nutrient concentration reduction. However, the grazing pressure of zooplankton on phytoplankton also decreased markedly as judged from changes in the ratio of zooplankton biomass to phytoplankton biomass and Daphnia proportion of total zooplankton biomass. This is likely a response to increasing predation on zooplankton by the stocked fish. Our results also indicated that water temperature, total phosphorus and water level promoted phytoplankton growth. Our results revealed that filter-feeding fish contributed to the decline in the biomass of phytoplankton but that it also had a strong negative effect on the grazing pressure of zooplankton on phytoplankton, even in this deep reservoir where zooplankton may have a better chance of survival through vertical migration. The particular strong effect on zooplankton is most likely due to imbalance of stocking and harvesting of fish. In the management of eutrophic reservoirs, the reduction of external nutrient loading should have highest priority. In highland (low temperature) deep-water eutrophic reservoirs, stocking of filter-feeding fish may help to control filamentous phytoplankton provided that the fish stocking is properly managed. The optimal stocking intensity of filter-feeding fish that can help control phytoplankton in such reservoirs without excessive impact on large-bodied zooplankton is a topic for further elucidation, however.

Synergistic optimization of bio–oil quality and heavy metal solidification during microwave co–pyrolysis of cow dung and red mud - Jiaman Sun; Jinlin Tao; Rui Ma; Junhao Lin; Juan Luo; Shichang Sun; Ning Ma (Chemosphere, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Superhydrophobic MOF based materials and their applications for oil-water separation - Yijun Liu; Zhengda Lin; Yang Luo; Rui Wu; Rui Fang; Ahmad Umar; Zhongming Zhang; Zhiying Zhao; Jie Yao; Shuaifei Zhao (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Essential oil from Artemisia argyi alleviated liver disease in zebrafish (Danio rerio) via the gut-liver axis - Jianjie Chen; Shanshan Wu; Rui Wu; Honghu Ai; Xingru Lu; Jiaqi Wang; Yongju Luo; Lijuan Li; Jinling Cao (Fish & Shellfish Immunology, 2023)

Discrete element modelling of the effect of aspect ratio on compaction and shear behaviour of aggregates - Rui Lu; Qiang Luo; Tengfei Wang; David P. Connolly; Kaiwen Liu; Chunfa Zhao (Computers and Geotechnics, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Microwave-catalyzed pyrolysis of waste engine oil using steel slag catalyst: Structure design and insights into the intrinsic mechanism of active catalytic sites and microwave absorption functions - Jiahui Hou; Junhao Lin; Lin Fang; Xi Zhang; Rui Ma; Juan Luo (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Do not ignore the effects of phosphorus and potassium addition on microbial carbon use efficiency - Chenyang Zhang; Liyang Sun; Yichao Rui; Yue Li; Yiqi Luo; Minggang Xu; Andong Cai (Global Change Biology, 2023)

Purification of conchocelis of Neoporphyra haitanensis by the method of dominant Bacteria enrichment comprehensive treatment - Mingjie Ma; Qiqin Liu; Lin Huang; Peng Zhang; Haimin Chen; Juanjuan Chen; Qijun Luo; Tiegan Wang; Rui Yang (Aquaculture, 2023)

A precise crop row detection algorithm in complex farmland for unmanned agricultural machines - Zhiwen Ruan; Penghao Chang; Shangqing Cui; Jiaqi Luo; Rui Gao; Zhongbin Su (Biosystems Engineering, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Study on high-value products of waste plastics from microwave catalytic pyrolysis: Construction and performance evaluation of advanced microwave absorption-catalytic bifunctional catalysts - Juan Luo; Guojin Gong; Rui Ma; Shichang Sun; Chongwei Cui; Han Cui; Jiaman Sun; Ning Ma (Fuel, 2023)

Physicochemical properties and in vitro digestion behavior of emulsion gels stabilized by rice bran protein aggregates: Effects of heating time and induction methods - Yongxue Luo; Kexin Wang; Rui Pan; Ting Li; Qingjie Sun; Chuanfen Pu; Wenting Tang (Food Research International, 2023)

Selective pollutant degradation with a novel persulfate activation cell resistant to environmental interference - Hui-Shan Meng; Shu-Zhen He; Mei-Mei Wang; Jia-Rui Xi; Jia-Tai Wen; Hong-Wei Luo; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Preparation of bio-jet fuels by a controllable integration process: Coupling of biomass fermentation and olefin polymerization - Yuehui Luo; Rui Zhang; Yuting He; DanFeng Lou; Rui Zhu; Can Zhu; Minghui Fan; Quanxin Li (Bioresource Technology, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Correction to: Uncertain role of clouds in shaping summertime atmosphere‑sea ice connections in reanalyses and CMIP6 models - Rui Luo; Qinghua Ding; Ian Baxter; Xianyao Chen; Zhiwei Wu; Mitchell Bushuk; Hailong Wang (Climate Dynamics, 2023)

Uncertain role of clouds in shaping summertime atmosphere-sea ice connections in reanalyses and CMIP6 models - Rui Luo; Qinghua Ding; Ian Baxter; Xianyao Chen; Zhiwei Wu; Mitchell Bushuk; Hailong Wang (Climate Dynamics, 2023)
Downwelling longwave radiation (DLR) driven by the atmospheric and cloud conditions in the troposphere is suggested to be a dominant factor to determine the summertime net surface energy budget over the Arctic Ocean and thus plays a key role to shape the September sea ice. We use reanalyses and the self-organizing map (SOM) method to distinguish CMIP6 model performance in replicating the observed strong atmosphere-DLR connection. We find all models can reasonably simulate the linkage between key atmosphere variables and the clear sky DLR but behave differently in replicating the atmosphere-DLR connection due to cloud forcing. In ERA5 and strongly coupled models, tropospheric high pressure is associated with decreased clouds in the mid- and high-levels and increased clouds near the surface. This out-of-phase structure indicates that DLR cloud forcing is nearly neutral, making the clear sky DLR more important to bridge JJA circulation to late-summer sea ice. In MERRA-2 and weakly coupled models, tropospheric clouds display a vertically homogeneous reduction; the cloud DLR is thus strongly reduced due to the cooling effect, which partially cancels out the clear sky DLR and makes the total DLR less efficient to translate circulation forcing to sea ice. The differences of cloud vertical distribution in CMIP6 appear to be differentiated by circulation related relative humidity. Therefore, a better understanding of the discrepancy of different reanalyses and remote sensing products is critical to comprehensively evaluate simulated interactions among circulation, clouds, sea ice and energy budget at the surface in summer.

Confining stress effects on global and local responses of internal erosion in gap-graded cohesionless soils - LiangLiang Zhang; Gang Deng; Rui Chen; ZhiYuan Luo (Bulletin of Engineering Geology and the Environment, 2023)

The interference between effects of PFAS exposure on thyroid hormone disorders and cholesterol levels: an NHANES analysis - Liang Zheng; Zhecun Wang; Rui Yang; Wanna Chen; Jing Zhang; Ruixia Li; Weiming Lv; Bo Lin; Jiajun Luo (Environmental Science and Pollution Research, 2023)

Overexpression of CdtCIPK21 from triploid bermudagrass reduces salt and drought tolerance but increases chilling tolerance in transgenic rice - Rui Liu; Shilian Huang; Anyao Huang; Miao Chen; Yurong Luo; Zhenfei Guo; Shaoyun Lu (Journal of Plant Physiology, 2023)

Inhibitory effect of polyethylene microplastics on roxarsone degradation in soils - Jie-wen Ma; Ya-qing Wu; Chen-Lu Xu; Zhuan-xi Luo; Rui-lian Yu; Gong-ren Hu; Yu Yan (Journal of Hazardous Materials, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Resistant starch formation mechanism of amylosucrase-modified starches with crystalline structure enhanced by hydrothermal treatment - Ren Wang; Pinxin Rui; Tao Wang; Wei Feng; Zhengxing Chen; Xiaohu Luo; Hao Zhang (Food Chemistry, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Ball-milling-induced phase transition of ZrO2 promotes selective oxidation of glycerol to dihydroxyacetone over supported PtBi bimetal catalyst - Pan Luo; Jianyue Wang; Wenjuan Rui; Ruilin Xu; Zhiyuan Kuai; Dan Yang; Xiaoyue Wan; Chunmei Zhou; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Microorganisms, their residues, and soil carbon storage under a continuous maize cropping system with eight years of variable residue retention - Xuefeng Zhu; Hongtu Xie; Michael D. Masters; Yichao Rui; Yu Luo; Hongbo He; Xudong Zhang; Chao Liang (Applied Soil Ecology, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Lower limits of petrophysical parameters for effective reservoirs in ultradeep carbonate gas reservoirs: A case study from the Deng IV Member, Gaoshiti-Moxi Area, Sichuan Basin, SW China - Lu Wang; Yifan Zhang; Ruilan Luo; Rui Zou; Hui Deng; Run Zou; Liang Huang; Yisheng Liu (Journal of Hydrology, 2023)

Water stable isotope characteristics and water use strategies of co-occurring plants in ecological and economic forests in subtropical monsoon regions - Junjie Dai; Xinping Zhang; Li Wang; Rui Wang; Zidong Luo; Xinguang He; Zhiguo Rao (Journal of Hydrology, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Microwave-induced preparation of MgO-loaded N-rich porous biochar from marine biomass for efficient CO2 capture and mechanism exploration via theoretical calculation - Juan Luo; Yi Chen; Xi Zhang; Rui Ma; Huimin Huang; Shichang Sun; Junhao Lin; Feng Yan; Jiyun Xu (Journal of Cleaner Production, 2023)

Bacterial microbiota and metabolic characteristics of traditional Zhangjiajie Jiuqu aromatic ester vinegar in China - Yue Sun; Xinyu Zuo; Rui Luo; Na Dang; Di Shi; Wenjun Liu (Food Bioscience, 2023)

Immunoregulatory hydrogel decorated with Tannic acid/Ferric ion accelerates diabetic wound healing via regulating Macrophage polarization - Na Xu; Yuanping Gao; Zheng Li; Yu Chen; Menglong Liu; Jiezhi Jia; Rui Zeng; Gaoxing Luo; Jiangfeng Li; Yunlong Yu (Chemical Engineering Journal, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Electron transport engineering of carbon hybrid network towards physiological signal monitoring and efficient heat management - Yan Luo; Wei Cao; Kaili Wu; Huinan Wang; Xin Wang; Huijuan Lin; Kun Rui; Yan Yan; Jixin Zhu (Chemical Engineering Journal, 2023)

Research progress of volatile organic compounds produced by plant endophytic bacteria in control of postharvest diseases of fruits and vegetables - Lijun Ling; Yuanyuan Wang; Wenting Cheng; Kunling Jiang; Hong Luo; Mingmei Pang; Rui Yue (World Journal of Microbiology and Biotechnology, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

A Novel Method for Determining the Three-dimensional Roughness of Rock Joints Based on Profile Slices - Changshuo Wang; Rui Yong; Zhanyou Luo; Shigui Du; Murat Karakus; Chuxia Huang (Rock Mechanics and Rock Engineering, 2023)

Measuring static and dynamic industrial eco-efficiency in China based on the MinDS–Malmquist–Luenberger model - Pei-Pei Jiang; Yuan Wang; Jin Luo; Lin Zhu; Rui Shi; Song Hu; Xiaodong Zhu (Environment, Development and Sustainability, 2023)

Effects of polystyrene nanoplastic gestational exposure on mice - Xiaoke Wang; Zixuan Zhao; Xin Wang; Wenxuan Hu; Chao luo; Xiuyu Chu; Muzhou Qian; Rui Wang; Shali Yu; Qiyun Wu; Juan Tang; Xinyuan Zhao (Chemosphere, 2023)

Effects of saline-alkali stress on the tissue structure, antioxidation, immunocompetence and metabolomics of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Science of The Total Environment, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

A dispersive solid-phase extraction method for the determination of Aristolochic acids in Houttuynia cordata based on MIL-101(Fe): An analytes-oriented adsorbent selection design - Rui Cheng; Xuejin Mao; Jiaying Yu; Fan Liu; Lan Guo; Dongmei Luo; Yiqun Wan (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Methodological and reporting quality evaluation of Buyang Huanwu decoction for experimental cerebral ischemia–reperfusion injury: a systematic review - Xiangyu Chen; Tong Yang; Yanan Luo; Zhitao Feng; Rui Fang; Jinwen Ge; Zhigang Mei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Buyang Huanwu decoction, a classic traditional Chinese prescription, has been used to prevent and treat stroke for hundreds of years. An increasing number of the laboratory research on Buyang Huanwu decoction used in treating cerebral ischemia–reperfusion injury have been published recently. However, the problem of methodological and reporting quality of some studies is lack of assessment. This study aims to evaluate the methodological and reporting quality of the research on Buyang Huanwu decoction against experimental cerebral ischemia–reperfusion injury. A comprehensive search on six databases was performed. Two researchers independently screened the literature considering the eligibility criteria. Methodological and reporting quality of the included studies were evaluated by the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) risk-of-bias tool and Animal Research: Reporting of In Vivo Experiments (ARRIVE) guideline. Forty-five studies met the inclusion criteria. No study achieved a decent overall rating in using the SYRCLE tool (percentage of items with “low risk” ≥ 50%). Of the 22 items on the SYRCLE tool, only 7 items (31.82%) were rated as “low risk” in more than 50% of the included studies. Of the 39 items of ARRIVE guideline, 14 (35.9%) items were rated as “yes” in more than 50% of the included studies. The methodological and reporting quality of Buyang Huanwu decoction for experimental cerebral ischemia–reperfusion injury was substandard, which needed to be further improved. The limitations should be addressed when planning similar studies in the future. Additionally, these findings provided evidence-based guidance for future preclinical studies evaluating the efficacy of Buyang Huanwu decoction in the treatment of cerebral ischemia–reperfusion injury.

Hcprismatin-14 of Hyriopsis cumingii, a novel matrix protein is crucial for framework recognition and crystal deposition during prismatic layer formation - Can Jin; Yihang Zhang; Kang Cheng; Rui Jiang; Shangning Jiang; Yezhong Shi; Gang Ren; Wen Luo (Frontiers in Marine Science, 2023)
Mollusk shells are characterized by hierarchical aggregation of calcium carbonate and organic matrix, and matrix protein is considered as a key active ingredient to understand shell biomineralization. In this study, a total of 21 proteins, including a novel matrix protein Hcprismatin-14 were identified in the EDTA-soluble matrix of the prismatic layer of the mussel Hyriopsis cumingii by liquid chromatography tandem mass spectrometry (LC-MS/MS). The full length of Hcprismatin-14 cDNA was cloned from the mantle of H. cumingii . Hcprismatin-14 contains a high proportion of Gly, Tyr, Arg and Asp residues, their concentrated distribution forms three structurally characteristic regions: a Gly/Tyr-rich region, a WDD-repeat region and a C-terminal basic tail. Hcprismatin-14 expression was high in mantle edge tissue in a tissue-specific analysis, and during disordered crystal deposition in a saibo transplantation assay. Knocking down Hcprismatin-14 expression with double-stranded RNA induced subgrains deposition inhibition and lost contact with chitinous scaffold. In addition, the WDD-repeat region polypeptide was involved in morphological regulation of calcite and had dose-dependent inhibitory activity against aragonite deposition in vitro . Based on these results, Hcprismatin-14 appears to be a dual-function prismatic-layer matrix protein, responsible for both framework recognition and crystal deposition. These findings contribute to understanding the relationship between the modular structure of matrix protein and their regulation mechanism during shell biomineralization in mollusks.

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Residual strength prediction of X80 steel pipelines containing group corrosion defects - Rui Zhou; Xiaoting Gu; Xi Luo (Ocean Engineering, 2023)

Evaluation of novel isolates of Lacticaseibacillus rhamnosus Probio-M9 derived through space mutagenesis - Jingfang Yang; Yue Sun; Xueyan Lei; Lixia Zhao; Rui Luo; Wenjun Liu (Food Bioscience, 2023)

Preparation of high performance porous carbon by microwave synergistic nitrogen/phosphorus doping for efficient removal of Cu2+ via capacitive deionization - Huimin Huang; Yi Chen; Rui Ma; Juan Luo; Shichang Sun; Junhao Lin; Yanyi Wang (Environmental Research, 2023)

The role of intercellular junction proteins in the penetration resistance of Drosophila larvae to avermectin - Li-Ping Chen; Han-Qing Jiang; Liang Luo; Jun Qiu; Xue-Jie Xing; Rui-Yan Hou; Yi-Jun Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

Using oligoagar to improve the survival of Neoporphyra haitanensis conchocelis infected by Vibrio mediterranei 117-T6 - Yangying Mao; Rui Yang; Lei Ke; Haimin Chen; Juanjuan Chen; Qijun Luo (Journal of Applied Phycology, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Characteristics, sources and health risk assessment of atmospheric carbonyls during multiple ozone pollution episodes in urban Beijing: Insights into control strategies - Yunfeng Li; Hong Li; Xin Zhang; Yuanyuan Ji; Rui Gao; Zhenhai Wu; Manfei Yin; Lei Nie; Wei Wei; Guohao Li; Yafei Wang; Mei Luo; et al. (Science of The Total Environment, 2023)

Comparison of travel-time and geostatistical inversion approaches for hydraulic tomography: Synthetic modeling study on data density and well configuration issues - Huiyang Qiu; Rui Hu; Ning Luo; Walter A. Illman; Xiaolan Hou (Journal of Hydrology, 2023)

Effects of vacuum drying assisted with condensation on drying characteristics and quality of apple slices - Xin Bao; Rui Min; Kai Zhou; Maria Victoria Traffano-Schiffo; Quan Dong; Wei Luo (Journal of Food Engineering, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Tectonic boundaries in the South China Sea from aeromagnetic signature - Yao Luo; Hang Yin; Qiang Liu; Jingmin Li; Shihua Liu; Wei Gao; Rui Li; Yi Yang (Journal of Oceanology and Limnology, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Effects of microwave and plastic content on the sulfur migration during co–pyrolysis of biomass and plastic - Jiaman Sun; Juan Luo; Rui Ma; Junhao Lin; Lin Fang (Chemosphere, 2023)

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

The effects of salt flow on the cross-section restoration of salt-bearing fold-and-thrust belts: An example from the Kuqa depression - Wanhui He; Wei Wang; Huiwen Xie; Hongwei Yin; Dong Jia; Zhenping Xu; Haoyu Luo; Rui Yuan (Journal of Structural Geology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Numerical investigation of a 1MW full-loop chemical looping combustion unit with dual CFB reactors - Liyan Sun; Rui Xiao; Junjie Lin; Dali Kong; Kun Luo; Jianren Fan (International Journal of Greenhouse Gas Control, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

SnO2/ATP catalyst enabling energy-efficient and green amine-based CO2 capture - Zhan Tan; Shangshang Zhang; Fangfang Zhao; Rui Zhang; Feiying Tang; Kuiyi You; He'an Luo; Xiaowen Zhang (Chemical Engineering Journal, 2023)

Upregulation LncRNA MEG3 expression suppresses proliferation and metastasis in melanoma via miR-208/SOX4 - Yi Yang; Liang Jin; Juan He; Rui Wang; Yilin Wang; Jia Bai; Youbai Chen; Zhanpeng Luo (Molecular and Cellular Biochemistry, 2023)

The protective effect of drying on the cryopreservation of Neoporphyra haitanensis - Haike Qian; Qijun Luo; Juanjuan Chen; Rui Yang; Tiegan Wang; Peng Zhang; Haimin Chen (Journal of Applied Phycology, 2023)

A combined surface-enhanced Raman spectroscopy (SERS)/colorimetric approach for the sensitive detection of malondialdehyde in biological samples - Xiaojun Luo; Shutong Zhang; Zhichao Xia; Rui Tan; Qiuju Li; Ling Qiao; Yi He; Guoqi Zhang; Zhihong Xu (Analytica Chimica Acta, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Recycling utilization of Chinese medicine herbal residues resources: systematic evaluation on industrializable treatment modes - Jiahao Luo; Rui Yang; Feifei Ma; Wenming Jiang; Chunchao Han (Environmental Science and Pollution Research, 2023)

Protective effect of Sargassum fusiforme polysaccharides on H2O2-induced injury in LO2 cells - Jiarui Li; Zhuo Wang; Jianping Chen; Baozhen Luo; Xuehua Chen; Rui Li; Jialong Gao; Xiaofei Liu; Bingbing Song; Saiyi Zhong (Frontiers in Marine Science, 2023)
Introduction Sargassum fusiform is considered a traditional Chinese medicinal herb to treat many diseases, Sargassum fusiform polysaccharides (SFPS) were found to display many important biological activities. The purpose of this study was to investigate the in vitro antioxidant activity of crude polysaccharide from Sargassum fusiforme and its protective effect against H 2 O 2 -induced injury in LO2 cells. Methods SFPS was extracted from Sargassum fusiforme using water extraction and alcohol precipitation. High-performance liquid chromatography (HPLC) was used to measure its monosaccharide composition. The in vitro antioxidant activity of SFPS was evaluated using scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical assays. Moreover, its hepatoprotective activity was examined by establishing H 2 O 2 -induced LO2 cells injury model. Results and discussion The results showed that the SFPS was composed of Glc, Ara, Fuc, Gal, Man, Rha and Xyl. Meanwhile, SFPS exhibited strong antioxidant activity and potential hepatoprotective effect. Further studies found that SFPS could alleviate LO2 cells injury induced by H 2 O 2 via decreasing malondialdehyde (MDA) and lactate dehydrogenase (LDH) levels, increasing superoxide dismutase (SOD) and catalase (CAT) activities and inhibiting intracellular reactive oxygen species (ROS) production. These results revealed that SFPS had the ability to protect the liver cells from H 2 O 2 -induced liver injury through its antioxidant activity.

A hormesis-like effect of FeS on heterotrophic denitrification and its mechanisms - Yunyi Zha; Rui Wan; Mengqi Wu; Ping Ye; Liangtao Ye; Xiaoxiao Li; Haifeng Yang; Jingyang Luo (Chemosphere, 2023)

Immune and intestinal microbiota responses to heat stress in Chinese mitten crab (Eriocheir sinensis) - Zhiqiang Li; Zhigang Zhao; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Yuhong Yang (Aquaculture, 2023)

Salicylic acid enhances the resistance of Neoporphyra haitanensis to pathogen Vibrio mediterranei 117-T6 - Shanshan Zhu; Zhen Jin; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Aquaculture, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

OsHLS1 regulates plant height and development by controlling active gibberellin accumulation in rice (Oryza sativa L.) - Tonghua Zhang; Jiafu Wang; Rui Luo; Jianmin Man; Qing Long; Ning Xu (Plant Science, 2023)

Who takes the lead? A disaggregate analysis of the EU's engagement in the Clean Energy Ministerial and Mission Innovation - Jale Tosun; Christin Heinz-Fischer; Rui Luo (Journal of Cleaner Production, 2023)

Dual function intensified cracking of waste engine oil to produce alkane-rich oil: Study on the synergistic effect of Fe-Co/MCM41 catalyst and microwave - Guojin Gong; Juan Luo; Shichang Sun; Junhao Lin; Rui Ma; Jiaman Sun (Fuel, 2023)

Experimental and theoretical study on the transformation of typical organic sulfur during hydrothermal carbonization of sludge - Shan Cheng; Jingchun Huang; Rui Luo; Hong Tian; Yanshan Yin; Yu Qiao (Fuel, 2023)

Metabolomics analysis reveals the response mechanism to carbonate alkalinity toxicity in the gills of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Construction of polyphosphazene-functionalized Ti3C2TX with high efficient flame retardancy for epoxy and its synergetic mechanisms - Hao Jiang; Yuhui Xie; Rui Zhu; Yong Luo; Xinxin Sheng; Delong Xie; Yi Mei (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Crosstalk between exosomes and autophagy in spinal cord injury: fresh positive target for therapeutic application - Rui-yu Li; Qi Hu; Xu Shi; Zhen-yu Luo; Dong-hua Shao (Cell and Tissue Research, 2023)
Spinal cord injury (SCI) is a very serious clinical traumatic illness with a very high disability rate. It not only causes serious functional disorders below the injured segment, but also causes unimaginable economic burden to social development. Exosomes are nano-sized cellular communication carriers that exist stably in almost all organisms and cell types. Because of their capacity to transport proteins, lipids, and nucleic acids, they affect various physiological and pathological functions of recipient cells and parental cells. Autophagy is a process that relies on the lysosomal pathway to degrade cytoplasmic proteins and organelles and involves a variety of pathophysiological processes. Exosomes and autophagy play critical roles in cellular homeostasis following spinal cord injury. Presently, the coordination mechanism of exosomes and autophagy has attracted much attention in the early efficacy of spinal cord injury. In this review, we discussed the interaction of autophagy and exosomes from the perspective of molecular mechanisms, which might provide novel insights for the early therapeutic application of spinal cord injury.